Self-assembled monolayers of peptide nucleic acids on gold surfaces a spectroscopic study - Mateo-Martí, E (Langmuir : the ACS journal of surfaces and colloids, 2005)
We have characterized self-assembled monolayers (SAMs) of thiol-derivatized peptide nucleic acid (PNA) chains adsorbed on gold surfaces by using reflection absorption infrared spectroscopy (RAIRS) and X-ray photoemission spectroscopy (XPS) techniques. We have found that the molecular orientation of PNAs strongly depends on surface coverage. At low coverage, PNA chains lie flat on the surface, while at high coverage, PNA molecules realign their molecular axes with the surface normal and form SAMs without the need of co-immobilization of spacers or other adjuvant molecules. The change in the molecular orientation has been studied by infrared spectroscopy and it has been confirmed by atomic force microscopy (AFM). PNA immobilization has been followed by analyzing the N(1s) XPS core-level peak. We show that the fine line shape of the N(1s) core-level peak at optimal concentration for biosensing is due to a chemical shift. A combination of the above-mentioned techniques allow us to affirm that the structure of the SAMs is stabilized by molecule-molecule interactions through noncomplementary adjacent nucleic bases